Synergistic effects of earthworms and cow manure under reduced chemical fertilization modified microbial community structure to mitigate continuous cropping effects on Chinese flowering cabbage - Gao, Fucheng; Ye, Lin; Mu, Xiaoguo; Xu, Lei; Shi, Zhenfang; Luo, Yuan (Frontiers in Microbiology, 2023)
The substitution of chemical fertilizers with organic fertilizers is a viable strategy to enhance crop yield and soil quality. In this study, the aim was to investigate the changes in soil microorganisms, soil chemical properties, and growth of Chinese flowering cabbage under different fertilization treatments involving earthworms and cow manure. Compared with the control (100% chemical fertilizer), CE (30% reduction in chemical fertilizer + earthworms) and CFE (30% reduction in chemical fertilizer + cow dung + earthworms) treatments at soil pH 8.14 and 8.07, respectively, and CFC (30% reduction in chemical fertilizer + cow manure) and CFE treatments increased soil organic matter (SOM), total nitrogen (TN), available nitrogen (AN), and available potassium (AK) contents. Earthworms and cow manure promoted the abundance of Bacillus and reduced that of the pathogens Plectosphaerella and Gibberella. The mantle test revealed that pH was not correlated with the microbial community. Random forest analysis verified that AN, SOM, and TN were important factors that jointly influenced bacterial and fungal diversity. Overall, the synergistic effect of earthworms and cow manure increased soil fertility and microbial diversity, thereby promoting the growth and development of Chinese flowering cabbage. This study enhanced the understanding of how bioregulation affects the growth and soil quality of Chinese flowering cabbage, and thus provided a guidance for the optimization of fertilization strategies to maximize the yield and quality of Chinese flowering cabbage while reducing environmental risks.